EIB Working Paper 2022/14 - The scarring effects of major economic downturns - European Investment Bank (European Investment Bank, 2022)
"Despite the efforts of policy makers to tackle recessions as they happen, there is ample evidence that major economic downturns produce lasting negative effects on real GDP, pointing to the existence of “economic scarring”. This paper takes a fresh look at economic scarring in 26 OECD countries, including 14 EU member states, since 1970 and examines the role played by fiscal policy in limiting these impacts. It finds that higher current expenditure does not mitigate the lasting impact of major economic downturns on real GDP. By contrast, more government investment could help to do so, but this is generally less favoured as a policy response. As a result, scarring effects are significant, confronting governments with higher debt levels, which in turn weigh on the room for manoeuvre in subsequent downturns. In sum, fiscal policy makers face two difficulties in the event of a major economic downturn: adopting the right type of fiscal expansion, and finding the right time to pivot from short-term stabilisation to fiscal consolidation, while protecting investment."